Research on Performance of Fiber-Based Multiple Apertures Receiver System with PPM Modulation - Kangning LI; Xu FENG; Jianwen GAO; Jing Ma (天地一体化信息网络)
The performance of fi ber-based FSO with multiple apertures receiver system was studied for pulse position modulation (PPM) .Expressions of PPM modulated signal-to-noise ratio (SNR) and bit-error rate (BER) for fi ber-based FSO multiple apertures receiver system were presented based on the probability density function of Gamma-Gamma intencity distribution and non–central chisquare fi ber coupling effi ciency distribution under atmospheric infl uence.Selection combining (SC), equal gain combining (EGC) and maximum ratio combining (MRC) were considered to be three signal combining methods for multiple apertures receiver system.The BER performance of 4PPM modulted SC, EGC and MRC fi ber-based multiple apertures receiver system and single aperture receiver system with the same total aperture area were comparative analyzed by Monte Carlo simulation.The BER performance of fi ber-based multiple apertures receiver systems in 4PPM and 8PPM modulation modes were directly compared for diff erent combining methods.